(untitled) (Aporte Santiaguino, 2024)
This paper compiles the different environmental management instruments applicable to mining exploration projects, within the framework of obtaining environmental certification. Documentary research is used through the search, organization and analysis of information. Mining exploration projects can choose to manage up to 3 types of environmental management instruments: FTA, DIA, EIAsd as well as their respective modifications according to the requirements of the organization. From the analysis of the information, it is concluded that the evaluation times of the environmental management instruments stipulated in the sectorial regulations differ from the actual evaluation times in the case of the DIA, EIAsd and their modifications. It is expected that the results of this research will help in the optimization of the planning process of environmental permits for mining projects.